2009
DOI: 10.1038/jhh.2009.17
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between carotid artery stiffness index, BNP and high-sensitivity CRP

Abstract: Arterial stiffness is an independent predictor of cardiovascular morbidity and mortality. Brain natriuretic peptide (BNP) and high-sensitivity C-reactive protein (hs-CRP) are considered as novel biomarkers that are useful in the prediction of early cardiovascular risk. We studied the relationship between carotid artery stiffness index b and the cardiovascular biomarkers BNP and hs-CRP in 55 consecutive subjects. Carotid artery stiffness was assessed using the stiffness index b derived from brachial artery bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
1
12
0
1
Order By: Relevance
“…Other reports (30, 16) demonstrated that the arteries get stiffer with age, but those reports evaluated healthy patients in a broad age range (20 to 80 years of age). Patients evaluated in this work were all older than 50 years and had significant comorbidities that may have diminished the effect of age on the mechanical properties of the arteries tested.…”
Section: Discussionmentioning
confidence: 98%
“…Other reports (30, 16) demonstrated that the arteries get stiffer with age, but those reports evaluated healthy patients in a broad age range (20 to 80 years of age). Patients evaluated in this work were all older than 50 years and had significant comorbidities that may have diminished the effect of age on the mechanical properties of the arteries tested.…”
Section: Discussionmentioning
confidence: 98%
“…Hs-CRP, a plasma inflammation marker, has been known to play a role in the development of cardiovascular diseases and is considered as a biomarker that predicts early cardiovascular risk [22]. Several prospective epidemiological studies have demonstrated a consistent relationship between higher C-reactive protein (CRP) levels and an increased risk of cardiovascular events, including myocardial infarction, stroke, and cardiovascular death [23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…High-sensitivity C-reactive protein (hs-CRP), a plasma inflammation marker, has been known to play a role in the development of cardiovascular diseases and is considered as a biomarker that is useful in the prediction of early cardiovascular risk [14]. Several prospective epidemiological studies have demonstrated a consistent relationship between higher C-reactive protein (CRP) levels and increased risk of cardiovascular events, including myocardial infarction, stroke, and cardiovascular death [15,16].…”
Section: Introductionmentioning
confidence: 99%